Impact of Soil Saturation Level on the Dynamic Response of Masonry Buildings - Liratzakis, Alexandros; Tsompanakis, Yiannis (Frontiers in Built Environment, 2018)
The present study investigates the impact of the soil saturation level on the performance of unreinforced masonry (URM) buildings when subjected to seismic excitations. More specifically, this paper examines the dynamic response of an ordinary stone-built URM building, firstly in its initial state and subsequently when it is slightly retrofitted with reinforced concrete beams at the perimeter in both storeys and also reinforced concrete instead of wooden lintels above the openings. The assessment of the behavior of this typical URM building, taking into account the soil-structure interaction (SSI) along with the nonlinear behavior both of the soil and the structure is examined through incremental dynamic analyses. For this purpose, a compatible in terms of soil conditions, set of twenty ground motions was selected, each scaled to several levels of seismic intensity. Subsequently, multiple nonlinear dynamic analyses of the coupled model of soil and structure were performed. In addition, these calculations were repeated for eight different saturation levels covering a wide range of soil conditions to elaborately investigate the problem at hand.